A correlation between Magnetic Resonance Spectroscopy (1-H MRS) and the neurodevelopment of two-year-olds born preterm in an EPIRMEX cohort study - Gire, Catherine; Berbis, Julie; Dequin, Marion; Marret, Stéphane; Muller, Jean-Baptiste; Saliba, Elie; Tosello, Barthélémy (Frontiers in Pediatrics, 2022)
Background Preterm infants are at risk of neurodevelopmental impairments. At present, proton magnetic resonance spectroscopy (1H-MRS) is current used to evaluate brain metabolites in asphyxiated term infants. The purpose of this study was to identify in the preterm EPIRMEX cohort any correlations between (1H-MRS) metabolites ratio at term equivalent age (TEA) and neurodevelopmental outcomes at 2 years. Methods: Our study included EPIRMEX eligible patients who were very preterm infants (gestational age at birth ≤ 32 weeks) and who underwent a brain MRI at TEA and 1H-MRS using a monovoxel technique. The volumes of interest (VOI) were periventricular white matter posterior area and basal ganglia. The ratio of N Acetyl Aspartate (NAA) to Cho (Choline), NAA to Cr (creatine), Cho to Cr, and Lac (Lactate) to Cr were measured. Neurodevelopment was assessed at 24 months TEA with ASQ (Ages and Stages Questionnaire). Results: A total of 69 very preterm infants had a quantifiable 1H-MRS at TEA. In white matter there is a significant correlation between: 1) reduction in the NAA/Cho ratio and a total ASQ and/or abnormal communication score, 2) an increase in the Lact/Creat ratio and an abnormality of fine motor skills. In the grey nuclei there was a trend correlation between: 1) the reduction in the NAA/Cho ratio and sociability disorders; and 2) the increase in the Lact/Creat ratio and an anomaly in problem solving. Conclusions: Using NAA as a biomarker of vulnerability of immature oligodendrocytes in preterm children at TEA is correlate to neurodevelopment at two years. Similarly, the presence of lactate at TEA is abnormal for neurodevelopment at two years in the preterm brain.